72 weeks post-partum follow-up of dolutegravir versus efavirenz initiated in late pregnancy (DolPHIN-2): an open-label, randomised controlled study. Issue 8 (August 2022) - Malaba, Thokozile R; Nakatudde, Irene; Kintu, Kenneth; Colbers, Angela; Chen, Tao; Reynolds, Helen; Read, Lucy; Read, Jim; Stemmet, Lee-Ann; Mrubata, Megan; Byrne, Kelly; Seden, Kay; et al.
Summary: Background: Late initiation of antiretrovirals in pregnancy is associated with increased risk of perinatal transmission and higher infant mortality. We report the final 72-week postpartum results for efficacy and safety of dolutegravir-based compared with efavirenz-based regimens in mothers and infants. Methods: DolPHIN-2 was a randomised, open-label trial. Pregnant women in South Africa and Uganda aged at least 18 years, with untreated but confirmed HIV infection and an estimated gestation of at least 28 weeks, initiating antiretroviral therapy in third trimester were eligible for inclusion. Eligible women were randomly assigned (1:1) to receive either dolutegravir-based (50 mg dolutegravir, 300 mg tenofovir disoproxil fumarate, and either 200 mg emtricitabine in South Africa or 300 mg lamivudine in Uganda) or efavirenz-based (fixed dose combination 600 mg tenofovir disoproxil fumarate plus either emtricitabine in South Africa or lamivudine in Uganda) therapy. The primary efficacy outcome was the time to a viral load of less than 50 copies per mL measured at 6, 12, 24, 48, and 72 weeks postpartum with a Cox model adjusting for viral load and CD4 cell count. Safety endpoints were summarised by the number of women and infants with events. This trial is registered with ClinicalTrials.gov, NCT03249181 . Findings: Between Jan 23 and Aug 15, 2018, 280 women were screened for inclusion, of whom 268 (96%) women were randomly assigned: 133 (50%) to the efavirenz group and 135 (50%) to the dolutegravir group. 250 (93%; 125 [50%] in the efavirenz group and 125 [50%] in the dolutegravir group) women were included in the intention-to-treat analysis of efficacy. Median time to viral load of less than 50 copies per mL was 4·1 weeks (IQR 4·0–5·1) in the dolutegravir group compared with 12·1 weeks (10·7–13·3) in the efavirenz group (adjusted hazard ratio [HR] 1·93 [95% CI 1·5–2·5]). At 72 weeks postpartum, 116 (93%) mothers in the dolutegravir group and 114 (91%) in the efavirenz group had a viral load of less than 50 copies per mL. Of 57 (21%) mothers with a severe adverse event, three (2%) in the dolutegravir group and five (4%) in the efavirenz group were related to the drug (dolutegravir drug-related events were one woman each with suicidal ideation, suicide attempt, herpes zoster meningitis; efavirenz drug-related events were one woman each with suicide attempt and liver cirrhosis, and three people with drug-induced liver injury). Of 136 (56%) infants in whom severe adverse events were recorded, none were related to the study drugs. In addition to the three infant HIV infections detected at birth in the dolutegravir group that have been previously reported, an additional transmission in the efavirenz group occurred during breastfeeding despite optimal maternal viral suppression and serial negative infant tests in the first year of life. Interpretation: Dolutegravir was safe and well tolerated, supporting updated WHO treatment recommendations in pregnant and breastfeeding women. Infant HIV transmissions can occur during breastfeeding despite persistently undetectable maternal viral load highlighting the need for continued infant testing. Funding: Unitaid.